A Challenge to Conventional Fish Meal: Effects of Soy Protein Peptides on Growth, Histomorphology, Lipid Metabolism and Intestinal Health for Juvenile Pompano Trachinotus ovatus - Lin, Huaxing; Tan, Beiping; Ray, Gyan Watson; Zeng, Min; Li, Mei; Chi, Shuyan; Yang, Qihui (Frontiers in Marine Science, 2022)
This experiment was conducted to assess the possibility of replacing fish meal (FM) with soy protein peptide (SPP) at different levels—0% (FM), 14.29% (S5), 28.57% (S10), 57.14% (S20), 71.42%(S25)—and its effects on growth, histology, gene expression related to liver lipid metabolism and intestinal immunity in juvenile pompano Trachinotus ovatus (initial mean weight = 39.88 ± 0.15 g). 600 healthy and uniformed-size fish were distributed to five groups of three replicates, each with 40 fish in each floating cage and fed twice daily for 8 weeks. Results showed that no significant difference in the growth was observed with SPP replacing FM (P > 0.05). Serum glutathione peroxidase activity in the S10 group was significantly higher than that in the FM group, and serum malondialdehyde content significantly decreased (P < 0.05). SPP significantly improved intestinal immunity by increasing alkaline phosphatase and lysozyme activities and up-regulating interleukin 10 and complement 4 mRNA levels while simultaneously decreasing triglyceride and total cholesterol content and down-regulating interleukin 1β mRNA expression. Villus length and muscle thickness in the S10 group were significantly higher than those in the FM group (P < 0.05). SPP significantly improved liver fat metabolism by increasing carnitine palmitoyl transferase I mRNA levels, and down-regulating fatty acid synthesis mRNA expression (P < 0.05). In summary, SPP substitution for FM promoted intestinal health, liver lipid metabolism and reduced liver fat accumulation for juvenile pompano T. ovatus, with no significant effect on growth performance. Based on the second-order polynomial analysis model of LYZ activity, the optimal replacement SPP level for juvenile pompano T. ovatus was 11.82%.